2008
DOI: 10.1002/asjc.30
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized tracking control for linear uncertain interconnected systems with time delays

Abstract: This paper investigates the robust output tracking problem for a class of large-scale linear uncertain systems with interactions and time delays. Time delays exist in both states and controls. Using the Riccati equation, a procedure for determining decentralized linear control laws is presented such that the closed-loop system asymptotically tracks the reference output and rejects any constant but unknown disturbances. The main feature of this approach is that the uncertain systems may contain time delays in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…There are kinds of decentralized control schemes 12–21. To compare with the proposed decentralized control scheme, the commonly used diagonal blocked Lyapunov function method is introduced briefly in this subsection.…”
Section: The Decentralized Control For Lti Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…There are kinds of decentralized control schemes 12–21. To compare with the proposed decentralized control scheme, the commonly used diagonal blocked Lyapunov function method is introduced briefly in this subsection.…”
Section: The Decentralized Control For Lti Systemmentioning
confidence: 99%
“…The decentralized control is simpler and more practical than centralized control method since the information exchange among subsystems is not required. The relevant research results on decentralized control can be found in 12–21. The LMI‐based decentralized control methods for continuous‐time systems can be found in 14, 15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for recent awareness of nonlinear models is that they describe most physical systems and increase the accuracy and performance of system behavior. During recent decades, various types of adaptive controllers have been developed and applied, more particularly for smaller systems [35][36][37][38][39] and large-scale linear systems [2,5,[32][33][34], based on different approaches, such as, minimum variance [37,39], generalized minimum variance [2,38], decentralization [12], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of research effort has been devoted to the analysis and design of robust or H ∞ controllers for neutral delay systems 4–31. In general, the existing H ∞ control methods proposed for neutral delay systems can be featured as delay‐independent 4, 5, 8 or delay‐dependent 5–7, 9–11, 13, 15–17, 24–26, 30–32.…”
Section: Introductionmentioning
confidence: 99%